2022
DOI: 10.3390/jpm12040634
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesic Effectiveness of Peripheral Nerve Blocks in Cesarean Delivery: A Systematic Review and Network Meta-Analysis

Abstract: The purpose of this systematic review and network meta-analysis was to determine the analgesic effectiveness of peripheral nerve blocks (PNBs), including each anatomical approach, with or without intrathecal morphine (ITMP) in cesarean delivery (CD). All relevant randomized controlled trials comparing the analgesic effectiveness of PNBs with or without ITMP after CD until July 2021. The two co-primary outcomes were designated as (1) pain at rest 6 h after surgery and (2) postoperative cumulative 24-h morphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…Cesarean section can cause moderate to severe acute postoperative pain. Improper postoperative pain control may delay the mother's recovery, interfere with breastfeeding, and have a negative influence on mother-infant bonding ( 29 ). Therefore, it is important for anesthesiologists to seek optimal postoperative analgesia for parturients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section can cause moderate to severe acute postoperative pain. Improper postoperative pain control may delay the mother's recovery, interfere with breastfeeding, and have a negative influence on mother-infant bonding ( 29 ). Therefore, it is important for anesthesiologists to seek optimal postoperative analgesia for parturients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The previous recommendation is based on information obtained from a recent meta-analysis, Champaneria et al [24] state that TAP blocks significantly reduce pain and postoperative morphine consumption at rest both when compared with placebo or no TAP blocks, however, this significance is lost when compared to IT morphine or given in co-administration. Contrary to this, a recent network meta-analysis by Ryu et al [25] concluded that combined IT morphine in conjunction with ilioinguinal-iliohypogastric nerve and anterior transversus abdominis plane block was the most effective post-caesarean analgesic strategy with lower rest pain at 6 hours and cumulative 24-hour morphine consumption. Additionally, other effective options for effective analgesia were IT morphine, ilioinguinal-iliohypogastric nerve block with IT morphine, lateral TAP block, and Perioperative Analgesia in Caesarean Section: What's New?…”
Section: Transverse Abdominal Plane Blockmentioning
confidence: 92%
“…A cesarean section (CS) remains the most commonly performed procedure in the obstetric settings worldwide. However, pain after CS is a common problem, and moderate to severe pain has been reported in a large proportion of parturients ( Ryu et al, 2022 ). Establishing and maintaining adequate pain control after CS with minimal adverse reactions facilitates a rapid recovery to ambulate and baby care for parturients.…”
Section: Introductionmentioning
confidence: 99%